Anales de la Sociedad Científica Argentina
Volume 45 contains the results (organization, membership, etc., and some of the papers) of Congreso Científico Latino Americano; v. 69-70 contains the results (organization, membership, etc. and some of the papers) of the Congreso Científico Internacional Americano.